2006
DOI: 10.1016/j.geoderma.2005.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Soil micro- and mesopores studied by N2 adsorption and 129Xe NMR of adsorbed xenon

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 30 publications
1
18
0
1
Order By: Relevance
“…Besides the surface area also porosity determines the capacity of the mineral phase to adsorb and preserve OM from oxidation (Kaiser and Guggenberger, 2003;Mayer et al, 2004). As Fe and Al oxyhydroxides exhibit significant microporosity (Torrent et al, 1992;Filimonova et al, 2006), differences in the developing porous network with increasing soil age may be responsible for the increasing amounts of H 2 O 2 -resistant OC.…”
Section: Evolution Of Mineral Surface Area and Organic Coverage Of CLmentioning
confidence: 99%
“…Besides the surface area also porosity determines the capacity of the mineral phase to adsorb and preserve OM from oxidation (Kaiser and Guggenberger, 2003;Mayer et al, 2004). As Fe and Al oxyhydroxides exhibit significant microporosity (Torrent et al, 1992;Filimonova et al, 2006), differences in the developing porous network with increasing soil age may be responsible for the increasing amounts of H 2 O 2 -resistant OC.…”
Section: Evolution Of Mineral Surface Area and Organic Coverage Of CLmentioning
confidence: 99%
“…The soluble minerals in the DCB extraction method were identified as the main microporous phases in soil. Filimonova et al (Filimonova et al, 2006) demonstrated that the removal of iron oxides by DCB treatment decreases the SSA by up to 50%. In their study, the micropores completely vanished in two German luvisol and gleysol soils.…”
Section: Introductionmentioning
confidence: 99%
“…This approach fails, however, as a quantitative measure of surface composition in some soils because of the presence of micropores (b2 nm diameter) that are often associated with iron and aluminum hydrous oxides (e.g., Mödl et al, 2007). Soil minerals with high microporosity have higher C-constant values compared to the soil minerals without them (Mayer and Xing, 2001) and the micropores are preferentially covered with OM compared to other parts of mineral surfaces in sorption experiments (Kaiser and Guggenberger, 2003;Mikutta et al, 2004;Filimonova et al, 2006). In addition, removal of OM by wet or dry oxidation treatments causes alteration and destruction of the micropores, reducing both SSA and C-constant (Mayer and Xing, 2001;Kaiser and Guggenberger, 2003;Filimonova et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Soil minerals with high microporosity have higher C-constant values compared to the soil minerals without them (Mayer and Xing, 2001) and the micropores are preferentially covered with OM compared to other parts of mineral surfaces in sorption experiments (Kaiser and Guggenberger, 2003;Mikutta et al, 2004;Filimonova et al, 2006). In addition, removal of OM by wet or dry oxidation treatments causes alteration and destruction of the micropores, reducing both SSA and C-constant (Mayer and Xing, 2001;Kaiser and Guggenberger, 2003;Filimonova et al, 2006). Nevertheless, a soil with full organic coverage of mineral surfaces can still be identified via a low C-constant of the untreated soil sample (i.e.…”
Section: Introductionmentioning
confidence: 99%